Desenvolvimento e aplicação de microplumas para tratamento de politereftalato de etileno (PET) - Silva, Lucas José da [UNESP] (2015)
This work describes the development and characterization of a microplasma jet device operating at atmospheric pressure and its application on the treatment of a polymeric surface. The micro discharge was produced between a needle and a coaxial cylindrical electrode with a borosilicate or quartz capillary between them. The discharge occurs in a small gap between the capillary and the needle and a plasma plume is produced at the tip of the needle. The signal used to excite the discharge was sinusoidal at frequency of 37 kHz. Breakdown voltage measurement showed distinct regimes according to the axial position of the cylinder relative to the needle. Simulations showed different equivalent circuits for the device according to the relative position between the electrodes. The plasma plumes were used to treat PET surfaces. It was observed the reduction of the contact angle with the treatment time that saturates around 10 s. The contact angle measurements at different positions around the treatment point were fitted using Gaussian and Lorentzian functions in order to estimate the diameter of treated circular area around the contact point of the plume with the surface. It was observed an increase of the treated area with the flow rate gas particularly at high applied voltage. Diameter up to 6 mm was achieved for plasma plumes with diameter smaller than 1 mm due to gas dynamic effects. The repeatability on the treatment showed that the plasma jet is reliable to modify surface properties of materials